A secure and fast chaotic encryption algorithm using the true accuracy of the computer - Nkapkop, Jean de Dieu (Informatica, 2016)
A secure and fast cryptosystem for image encryption based on chaotic generators is proposed. The principle of the method is to use the permutation-diffusion scheme to create computationally secure encryption primitives using the true accuracy of the computer. In the permutation step, integer sequences obtained by the sorting of the solutions of chaotic Logistic map by descending order is used as the permutation key to shuffle the whole image. This stage substantially reduces the correlation between neighboring pixels. After, in order to increase the entropy of encrypted image, the iteration of the chaotic Skew Tent map is applied, with an exclusive-or scheme, to change the value of the entire pixel. Moreover, to further enhance the security of the cryptosystem, the keystream used in diffusion process is updated for each pixel and the computed encrypted pixel values depends on both the previously encrypted pixels and the random keystream. We proved that the cipher sequence of the algorithm is random and truly random by applying the NIST tests batteries and